Customer Perception towards the Internet Banking Services Performed by the Turkish Banking System - Aydın, Dilara (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The aim of this study is to investigate the customer perception towards the internet banking services and to identify the main factors affecting the usage of internet banking in Turkey. For that purpose, six hypotheses have been employed for the research methodology. Questionnaire has been prepared and conducted a survey in Izmir for the fieldwork. Out of all the surveys collected, 245 were usable and were compiled with SPSS 18.0. The finding of the study indicated that factors of cost, ease of use, security, accesibility were statistically significant and have positive effects on customer satisfaction. However, awareness factor has no effect on customer satisfaction of internet banking. As a result of the analysis, it is found that education levels affect the usage of the internet banking services in Turkey. Keywords:Internet banking, customer satisfaction, customer perception. ………………………………………………………………………………………………………………………… ÖZ: Bu araştırmanın amacı, Türkiye„deki banka kullanıcılarının internet bankacılığına karşı tutumlarını ve müşteri memnuniyetine etki eden faktörleri araştırmaktır. Bu çalışma, banka müşterilerine yönelik anket çalışması yapılarak değerlendirmeye alınmış ve elde edilen sonuçlar SPSS 18.0 programı ile analiz edilmiştir. Araştırma modeli çerçevesinde 6 hipotez oluşturulmuştur. Veri toplamak amacıyla anket formları Türkçe olarak hazırlanmış ve İzmir ilinde uygulanmıştır. Uygulanan anketlerin 245‟i araştırma çerçevesinde analiz için kullanılmıştır. Araştırma sonuçlarına göre algılanan kullanım kolaylığı, güven, maliyet ve erişilebilirlik faktörlerinin müşteri memnuniyeti üzerinde önemli ve pozitif etkisi olduğu görülürken farkındalık faktörünün müşteri memnuniyeti üzerinde bir etkisi olmadığı saptanmıştır. Ayrıca bireylerin eğitim seviyelerinin internet bankacılığı kullanımlarını etkilediği sonucuna varılmıştır. Anahtar Kelimeler: Müşteri memnuniyeti, internet bankacılığı, müşteri tutumları.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Internet banking - Banks and banking - Turkey; Electronic commerce - Turkey; Financial services industry - Marketing; Internet Banking, Customer Satisfaction, Customer Perception